The problems of families of children with disabilities and the role of the social work profession in alleviating them (Field Study in Erbil City) - قادر, أ.م.د. مهدي عباس; علی, د. سیروان ولی (Sulaimani Journal for Humanities, 2025)
The study attempted to detect the (socio-economic-psychological) problems facing families of children with disabilities and the role of social service in alleviating those problems The study was based on the analytical descriptive curriculum and the study community from the families of the disabled in Kurdistan is one of the attendees of institutions for the care of children with disabilities in Erbil centers, Sulaymaniyah, Dohuk, as for the study sample, it consisted of 60 families of reluctant, The study relied on a measure of the social, economic and psychological problems of disabled children's families social workers ", as well as interviews with 5 social workers working in disabled care institutions in which the field study was applied. The findings of the study found that: for the social problems of families with disabilities, it was found: families of children with disabilities face various and important social problems, including people's acceptance of the existence of disability, differences between family members due to disability, difficulty in participating in social activities, and the isolation of adverse children from society due to a family member's disability. As for the economic problems experienced by families of children with disabilities, it has emerged that the costs of education for children with disabilities are a heavy financial burden on families, that families find it difficult to cover the costs of treatment for their children with disabilities, and that families' income is insufficient to meet the needs of children with disabilities. As for the psychological problems experienced by the families of children with disabilities, they have been found to include: feeling pain when the child is ridiculed or people's gaze, feeling anxious about a risk that the child can face when he/she leaves the house, guilt because of their children's disability. In the light of those findings, a proposed vision has been built from a social service perspective to reduce the social, economic and psychological problems experienced by families of children with disabilities.
Keywords: Handicapped; disabled children; family; social work